Oral Lymphoma- A Short Review - Ryhanath Gulshan.F1 , K.M.K.Masthan2 , N.Aravindha Babu3, N.Anitha (Indian Journal of Forensic Medicine & Toxicology, 2020)
The malignant neoplasm of the lymphocyte cell lines are lymphomas. They are mainly classified as Hodgkin’sor non-Hodgkin’s lymphoma (NHL).The etiology is still unknown. Various treatment modalities causesacute and longer-term side-effects affecting the clinical decision-making for dental treatment. Therefore,people with lymphoma should have regular follow-up.